Ecology, conservation and management of the black lechwe (Kobus leche smithemani) in the Bangweulu Basin, Zambia - Van Hoven, Wouter (University of Pretoria, 2013)
Dissertation (MSc (Wildlife Management))--University of Pretoria, 2007.